THE EFFECTIVENESS OF PRACTICE AND COMMAND TEACHING-STYLE ON THE STUDY RESULT OF THE SHOT-PUT OF THE SMPN-2 SAMBA STUDENTS - Yossita Wisman (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
The purpose of this research is to find out the effectiveness of Practice and Command Teaching Style on the study result of the Shot-Put of the second semester eighth grader students in the SMPN-2 Katingan Tengah 2013. The research conducted at SMPN-2 Kecamatan Katingan Tengah, Katingan Regency academic calender 2013. The method used is an experiment method by collecting data on the pretest and post-test with the study result of the Shot-Put as the research instrument. The population in this research is all the students in the class which is 40 students, and the sample is the total of those students (total sample). This sample is divided into 2 groups by even and odd number. Even number group will apply command method and Odd number will apply practice method. The data will be analized using t-test with 5% level of confidence. The result of overall data analysis is as follows: the group with Command teaching style in the post-test has interval 68 to 85 and average value 75,55 while Practice teaching style has interval 67 to 90 and average value of 79,60. From the comparison of posttest between Command Teaching Style and Practice Teaching Style it is found that calculated-t is 2,471 which is bigger than table-t = 2,262 which means that there is a significant difference between those two groups. Therefore, it can be concluded that the null hypothesis (H0) which states that there is no significant difference is rejected and research hypothesis is accepted. It also means that Practice Teaching Style is more effective than Command Teaching Style on the study result of Shot-Put.